2004
DOI: 10.1104/pp.104.045724
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Stress. Activation of Distinct Mitogen-Activated Protein Kinase Pathways by Copper and Cadmium

Abstract: Excessive amounts of heavy metals adversely affect plant growth and development. Whereas some regions naturally contain high levels of heavy metals, anthropogenic release of heavy metals into the environment continuously increases soil contamination. The presence of elevated levels of heavy metal ions triggers a wide range of cellular responses including changes in gene expression and synthesis of metal-detoxifying peptides. To elucidate signal transduction events leading to the cellular response to heavy meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
201
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 390 publications
(209 citation statements)
references
References 47 publications
4
201
0
4
Order By: Relevance
“…It has been also suggested that Cd 21 can interfere in living cells with cellular redox reactions and displaces or releases other active metal ions (e.g. Zn 21 ) from various biological complexes, thereby causing a reduction of the capacity of the antioxidant system (Jonak et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been also suggested that Cd 21 can interfere in living cells with cellular redox reactions and displaces or releases other active metal ions (e.g. Zn 21 ) from various biological complexes, thereby causing a reduction of the capacity of the antioxidant system (Jonak et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In response to heavy metals, diverse signal transduction pathways are activated, including mitogenactivated protein kinases, transcription factors, and stress-induced proteins (Jonak et al, 2004). Our knowledge concerning components of these pathways is growing but still incomplete.…”
mentioning
confidence: 99%
“…It has been documented that mitogen-activated protein kinases (MAPKs) can perceive the changes of ROS content in signal transmission for a range of stresses 23 and the distinct MAPK pathways involve specifically to excess particular metal ions. [24][25][26] ROS induced by Cu triggers SIMK and SAMK activation via SIMKK, whereas Cd activates MMK2, MMK3 besides SIMK and SAMK. 24 Recently, MPK3 and MPK6 are also evidenced to be activated by Cd-induced ROS accumulation in Arabidopsis plants.…”
Section: Interactions Between Ros and Auxin Signaling In Plant Responmentioning
confidence: 99%
“…[24][25][26] ROS induced by Cu triggers SIMK and SAMK activation via SIMKK, whereas Cd activates MMK2, MMK3 besides SIMK and SAMK. 24 Recently, MPK3 and MPK6 are also evidenced to be activated by Cd-induced ROS accumulation in Arabidopsis plants. 25 A similar effect is also shown in plant response to Al stress, in which a MAPKlike protein is modulated by toxic concentrations of aluminum.…”
Section: Interactions Between Ros and Auxin Signaling In Plant Responmentioning
confidence: 99%
“…Recently, the effect of cadmium on plant MAPKs in rice suggests that a MAPK cascade may function in the cadmium-signaling pathway (Yeh et al, 2004). Copper and cadmium stress activate two distinct MAPK pathways in alfalfa (Medicago sativa) seedlings (Jonak et al, 2004). The regulation of PvSR2 expression by heavy metal represents a novel metalloregulatory system for investigation, particularly because it is one of the very few, if not the only, that focuses on specific responsiveness to heavy metal.…”
Section: The Function Of the Mre-like Sequence In Plantsmentioning
confidence: 99%